PENERAPAN METODE KLASIK PADA PEMBELAJARAN AL-QUR'AN DI MADRASAH IBTIDAIYAH NURUL ISLAM BANYU HIRANG GAMBUT - Ma'mun Syarif; Asmaran Asmaran (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
The background of this research is based on a reality that there are still Al-Qur'an education are applied by using a very classical method i.e. Qaidah Bagdhadiyah on formal school institution. Whereas during this period very many methods of learning the Qur'an, even assessed more effectively and efficiently. It is therefore very interesting to research about the process the application of classical methods Qaidah Bagdhadiyah and what factors affect its application in improving the quality of learning to read write the Qur'an in accordance with the expectations of society and Madrasah Ibtidaiyah educators Nurul Islam Banyu Hirang Gambut. The objectives to be achieved in this research is to explain the process of the application of classical methods to the study of Bagdhadiyah Al Qaidah Quran Madrasah Ibtidaiyah in Nurul Islam Banyu Hirang Gambut and the factors that influenced them. In this study data collection techniques used are observation, interview, and documentation. Based on the results of the research undertaken, it is known that the application of classical methods to the study of the Qur'an in the Madrasah Ibtidaiyah Nurul Islam Banyu Hirang Gambut can run well and is quite effective in accordance with nil the educational value of AI-Al-Quran Madrasah Ibtidaiyah developed at Nurul Islam Banyu Hirang Gambut. As for the factors that influence learning Quran Madrasah Ibtidaiyah in Nurul Islam Banyu Hirang Gambut is teacher factors, factors of students, infrastructure, media, as well as environmental factors and society. All these factors have strongly supported the implementation of the application of classical methods to the study of the Qur'an in the Madrasah Ibtidaiyah Nurul Islam Banyu Hirang Gambut. Keyword: Application, Classic Methods, Learning, The Qur'an, The Madrasah